2017
DOI: 10.1109/tpami.2016.2605085
|View full text |Cite
|
Sign up to set email alerts
|

Social Collaborative Filtering by Trust

Abstract: Recommender systems are used to accurately and actively provide users with potentially interesting information or services. Collaborative filtering is a widely adopted approach to recommendation, but sparse data and cold-start users are often barriers to providing high quality recommendations. To address such issues, we propose a novel method that works to improve the performance of collaborative filtering recommendations by integrating sparse rating data given by users and sparse social trust network among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
312
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(344 citation statements)
references
References 30 publications
2
312
0
1
Order By: Relevance
“…For the sake of generality, we consider only positive links in this study. The elimination of negative links is consistent with other studies [8], [12].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…For the sake of generality, we consider only positive links in this study. The elimination of negative links is consistent with other studies [8], [12].…”
Section: Introductionsupporting
confidence: 93%
“…Studies [10], [11], [8] suggested that user opinions are influenced by not only their own preferences but also their trusted friends. Social recommendation attracted a lot of attention in recent studies [6], [8], [12] and several e-commerce systems tried to leverage user social information to improve the quality of their recommender systems [11], [13].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance recommender systems with explicit social information, novel social recommendation models are studied in [3,4,9,10,11,14,20,22] [3], the authors proposed a trust-based MF technique by considering both the explicit and implicit influences of the neighborhood structure of user trust and the user-item ratings. Yang et al [20] designed a hybrid MF model that combines both a truster model and a trustee model with the assumption that a specific user's truster and trustee will affect their ratings. In [11], a user social regularization term is introduced to constrain the basic MF.…”
Section: Related Workmentioning
confidence: 99%
“…Various approaches [5,6,15,16,17,18] based on low-rank matrix factorization (MF) or Bayesian personalized ranking (BPR) have been proposed to solve the problems of ratings prediction or items ranking. To improve the recommendation performance, recent works [1,3,20,22] incorporate the observed explicit social information (e.g., trust connections of users) into MF or BPR frameworks to build novel systems (the so-called social recommender systems).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud service providers often hope to exploit the accumulated user-service quality data (i.e., users' experienced service quality) to assist in the decision of cloud service recommendation to provide better services or to maximize revenue. Specifically, a recommendation method, e.g., the seminal collaborative filtering (CF) [1], can be used directly on the data to find a target user's similar users (i.e., neighbors) based on historical user-service quality data.…”
Section: Introductionmentioning
confidence: 99%